1998
DOI: 10.1177/096973309800500604
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nurses in Euthanasia: a Dutch study

Abstract: What role do nurses play in euthanasia? How do they experience this role and what should be their ideal role? These are the questions of a study undertaken to gain insight into the role of nurses in euthanasia. Answers to these questions were derived from 20 semistructured in-depth interviews with nurses employed in a Dutch hospital. To make clear the role of nurses in euthanasia, the issue was split up into four phases: observation of a request for euthanasia; decision making; carrying out of the request; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
89
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 0 publications
1
89
0
1
Order By: Relevance
“…The different phases of the care process surrounding euthanasia are also described by Van de Scheur and Van der Arend. 9 Although presented artificially in our study as four different stages, the phases in the process are not strictly separate. We chose to present it this way to illustrate the special role of nurses in each stage of the euthanasia process.…”
Section: Discussionmentioning
confidence: 97%
“…The different phases of the care process surrounding euthanasia are also described by Van de Scheur and Van der Arend. 9 Although presented artificially in our study as four different stages, the phases in the process are not strictly separate. We chose to present it this way to illustrate the special role of nurses in each stage of the euthanasia process.…”
Section: Discussionmentioning
confidence: 97%
“…However, in most cultural contexts, nurses are the cornerstone of end-of-life care, as they play a key role in using a patient-centred approach to understand the wishes of patients and their families and to act on this understanding as advocates for patients and families in the decision-making process 16. As a consequence, nurses are frequently the first care givers to receive a patient’s request for euthanasia, and sometimes they are also involved in the decision-making process and in carrying out the request 711. Several studies have also suggested that nurses perform patient-requested euthanasia more frequently than physicians, occasionally without consulting a physician 1 12 13.…”
mentioning
confidence: 99%
“…This process comprises registering the request for euthanasia, participation in decision making, actually performing the euthanasia, and aftercare. 3 The nurse's involvement in euthanasia does not refer to the attitudes and ideas of nurses regarding euthanasia or their own involvement in it. Although these attitudes and ideas may conceivably exercise an influence on a nurse's factual involvement, they fall outside the scope of this literature review.…”
mentioning
confidence: 99%